2019
DOI: 10.1002/jcph.1447
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Selenomethionine on Thyroid Autoimmunity in Euthyroid Men With Hashimoto Thyroiditis and Testosterone Deficiency

Abstract: Hashimoto (autoimmune) thyroiditis develops much less frequently in men than in women, suggesting that androgens have a protective effect against thyroid autoimmunity. The current study was aimed at investigating whether the effect of selenomethionine on thyroid antibody titers and thyroid function tests in euthyroid men with autoimmune thyroid disease depends on testosterone levels. The study population consisted of 2 age‐matched, weight‐matched, and thyroid antibody titer–matched groups of euthyroid men with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In view of the former, further research is required to assess and clarify the efficacy and safety of Se supplementation in pregnancy to avoid adverse events. On the other hand, the effect of SeMet on the evolution of HT has been addressed in multiple publications, but its exact benefit and underlying immunological mechanism remain unclear [5,226,[248][249][250]. Data obtained from the SETI study indicate that short-term supplementation with SeMet resulted in a normalization of the TSH levels in 50% of the patients that presented subclinical hypothyroidism related to chronic AITDs.…”
Section: Selenomethionine and Autoimmune Thyroid Diseasesmentioning
confidence: 99%
“…In view of the former, further research is required to assess and clarify the efficacy and safety of Se supplementation in pregnancy to avoid adverse events. On the other hand, the effect of SeMet on the evolution of HT has been addressed in multiple publications, but its exact benefit and underlying immunological mechanism remain unclear [5,226,[248][249][250]. Data obtained from the SETI study indicate that short-term supplementation with SeMet resulted in a normalization of the TSH levels in 50% of the patients that presented subclinical hypothyroidism related to chronic AITDs.…”
Section: Selenomethionine and Autoimmune Thyroid Diseasesmentioning
confidence: 99%
“…Seleniummethionine (SeMet) is an organic selenium compound, and SeMet is often used to treat Se de ciency due to its low toxicity and easy absorption. SeMet has been found to have a variety of biological activities, including strengthening the immune system and improving antioxidant performance 10 . SeMet can reduce oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies showed that the pleiotropic effects of statins were contingent on normal thyroid hormone [2], prolactin [3,4] and vitamin D status [5], suggesting that hormone level irregularities may contribute to a dampened effect of statins on cardiometabolic risk factors. Patients with hypothyroidism or hyperprolactinemia on atorvastatin had smaller decreases in total and LDL cholesterol levels and a less pronounced decline in high sensitivity C-reactive protein (hsCRP), homocysteine, fibrinogen and uric acid levels when compared to their counterparts with normal thyroid hormone and prolactin levels [2,3]. Furthermore, patients with hypothyroidism were shown to have increased risk of statin-induced myopathy, possibly due to decreased cholesterol synthesis causing skeletal myocyte membrane instability [6].…”
mentioning
confidence: 99%
“…Earlier studies have demonstrated that statins provide a wide array of beneficial pleiotropic effects, including anti-inflammatory properties and endothelial-protective effects [1]. However, recent studies showed that the pleiotropic effects of statins were contingent on normal thyroid hormone [2], prolactin [3,4] and vitamin D status [5], suggesting that hormone level irregularities may contribute to a dampened effect of statins on cardiometabolic risk factors. Patients with hypothyroidism or hyperprolactinemia on atorvastatin had smaller decreases in total and LDL cholesterol levels and a less pronounced decline in high sensitivity C-reactive protein (hsCRP), homocysteine, fibrinogen and uric acid levels when compared to their counterparts with normal thyroid hormone and prolactin levels [2,3].…”
mentioning
confidence: 99%